Paternal mosaicism for a novel PBX1 mutation associated with recurrent perinatal death: Phenotypic expansion of the PBX1-related syndrome. - Arts, Peer; Garland, Jessica; Byrne, Alicia B; Hardy, Tristan S E; Babic, Milena; Feng, Jinghua; Wang, Paul; Ha, Thuong; King-Smith, Sarah L; Schreiber, Andreas W; Crawford, April; Manton, Nick; et al. (Am J Med Genet A, 2020)
Autosomal dominant (de novo) mutations in PBX1 are known to cause congenital abnormalities of the kidney and urinary tract (CAKUT), with or without extra-renal abnormalities. Using trio exome sequencing, we identified a PBX1 p.(Arg107Trp) mutation in a deceased one-day-old neonate presenting with CAKUT, asplenia, and severe bilateral diaphragmatic thinning and eventration. Further investigation by droplet digital PCR revealed that the mutation had occurred post-zygotically in the father, with different variant allele frequencies of the mosaic PBX1 mutation in blood (10%) and sperm (20%). Interestingly, the father had subclinical hydronephrosis in childhood. With an expected recurrence risk of one in five, chorionic villus sampling and prenatal diagnosis for the PBX1 mutation identified recurrence in a subsequent pregnancy. The family opted to continue the pregnancy and the second affected sibling was stillborn at 35 weeks, presenting with similar severe bilateral diaphragmatic eventration, microsplenia, and complete sex reversal (46, XY female). This study highlights the importance of follow-up studies for presumed de novo and low-level mosaic variants and broadens the phenotypic spectrum of developmental abnormalities caused by PBX1 mutations.
Keywords: Congenital Abnormalities; Exome; Fathers; Female; Gene Frequency; Humans; Infant, Newborn; Kidney; Male; Mosaicism; Mutation; Perinatal Death; Pre-B-Cell Leukemia Transcription Factor 1; Pregnancy; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing

Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

matchbox: An open-source tool for patient matching via the Matchmaker Exchange. - Arachchi, Harindra; Wojcik, Monica H; Weisburd, Benjamin; Jacobsen, Julius O B; Valkanas, Elise; Baxter, Samantha; Byrne, Alicia B; O'Donnell-Luria, Anne H; Haendel, Melissa; Smedley, Damian; MacArthur, Daniel G; Philippakis, Anthony A; et al. (Hum Mutat, 2018)
Rare disease investigators constantly face challenges in identifying additional cases to build evidence for gene-disease causality. The Matchmaker Exchange (MME) addresses this limitation by providing a mechanism for matching patients across genomic centers via a federated network. The MME has revolutionized searching for additional cases by making it possible to query across institutional boundaries, so that what was once a laborious and manual process of contacting researchers is now automated and computable. However, while the MME network is beginning to scale, the growth of additional nodes is limited by the lack of easy-to-use solutions that can be implemented by any rare disease database owner, even one without significant software engineering resources. Here, we describe matchbox, which is an open-source, platform-independent, portable bridge between any given rare disease genomic center and the MME network, which has already led to novel gene discoveries. We also describe how matchbox greatly reduces the barrier to participation by overcoming challenges for new databases to join the MME.